Development of force feedback in steering systems for virtual driving simulator - Setiawan, J.D. (EDP Sciences, 2018)
In steer-by-wire (SBW) vehicles, the elimination of the rigid mechanical column shaft would require the system to generate an artificial feedback torque which should produce similar driving feeling and behavior as to the conventional steering system. The objective of this study is to evaluate the characteristics of force feedback inside SBW vehicle for driving simulator utilizing Logitech G27 steering wheel. The model of the system is developed in Matlab/Simulink/3D Animation. A J-turn test is performed to see the resulting handwheel torque and its effect on the vehicle dynamic. The evaluation shows that the results are reasonable such that the driver of the simulator can feel the similar forces coming from the real road. Â© The Authors, published by EDP Sciences, 2018.